Iron oxide-loaded alginate-bentonite hydrogel beads as a green and sustainable catalyst for 4-nitrophenol reduction. (September 2021) - Biswas, Subhadeep; Pal, Anjali
Abstract: The development of sustainable green catalysts is always a challenging task. Besides this, the catalyst should be recyclable and hence cost-effective. In the present work, alginate hydrogel beads were used as a support of iron oxide to form iron oxide-loaded alginate beads (Io-alg). Alginate is a biopolymer, cheap, and nontoxic. Iron is abundant in nature and a non-toxic element. To improve the mechanical stability of the beads, bentonite was used to form iron oxide-loaded alginate-bentonite composite beads (Io-alg-ben). Bentonite is an inorganic material, easily available. Both Io-alg and Io-alg-ben beads in hydrogel conditions were deployed as the supported catalyst for the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) in borohydride environment. It is interesting to observe that hydrogel beads showed excellent catalytic activity toward 4-NP reduction. The zero-valent iron (ZVI) produced in-situ during the 4-NP reduction under NaBH4 medium was the active catalyst for 4-NP reduction. The reduction was examined using various catalyst doses and various initial concentrations of 4-NP, and in all cases the reaction followed zero-order kinetics. The catalyst could be reused up to 5 cycles without any loss of efficiency. The turnover number (TON) and turnover frequency (TOF) of the catalyst were found as 4.3 × 10 19 molecules/g and 3.09 × 10 17 molecules/g/s for Io-alg-ben hydrogel beads. The performance is comparable with other reported catalysts. The effect of reaction temperature was also investigated to find out the activation energy. Thus, a sustainable iron oxide-loaded alginate-bentonite supported catalyst has been developed for the efficient reduction of 4-NP to 4-AP. The novelty of the present work is that here the iron-oxide loaded alginate-bentonite hydrogel beads are stable, economical, nontoxic, and reusable for many cycles. Graphical Abstract: ga1 Highlights: Iron oxide-loaded alginate and alginate-bentonite hydrogel beads were prepared. Catalytic reduction of 4-nitrophenol reduction by borohydride was examined. Iron oxide-loaded hydrogel beads were used as the catalyst. Experimental data fits with zero order kinetics. Reusability of the catalyst was observed up to 5th cycle.